The evolution of socmed - Muhamad, Marlina (Universiti Teknologi MARA, Kedah, 2025)
The evolution of social media (coined as socmed) has grown from simple online platforms in the 1990s to complex ecosystems with profound societal and business impact. Here’s a breakdown of key milestones and distinctions in its evolution.